DAMPAK BEKERJA DARI RUMAH TERHADAP KEPEMILIKAN PSIKOLOGIS ORGANISASI. PERAN MEDIASI DARI KETERLIBATAN DAN STRESS KERJA. - Tuti Setyorini (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Working from home has become a very popular work arrangement system lately, especially during the Covid-19 pandemic. The purpose of this study was to examine the effect of the work from home system on organizational psychological ownership among workers in Indonesia. This study found that the effect of working from home system on psychological ownership is mediated by job involvement and stress. The theoretical and practical contributions are discussed in this study.